(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
A new Middle Triassic (Uppermost Anisian, Illyrian) gastropod genus and species, Rasatomaria gentilii gen. n. sp. n. , is described from the San Salvatore Formation from Rasa, an outer district of the town Varese (Lombardy, Italy). The studied specimens come from a diverse benthic marine assemblage, which is dominated by gastropods and bivalves. Based on ammonoids, this assemblage belongs to the Nevadites secedensis Zone. The new gastropod taxon is very low-spired, widely phaneromphalous, has a selenizone slightly above the periphery of the whorls and a dominant spiral ornament. It belongs to the superfamily Pleurotomarioidea and its knowledge improves our understanding of the Middle and Late Triassic radiation of this group.